Expression of the forkhead transcription factor FOXP1 is associated with estrogen receptor alpha and improved survival in primary human breast carcinomas. - Fox, S; Brown, P; Han, C; Ashe, S; Leek, R; Harris, A; Banham, A (2004)
PURPOSE: The FOXP1 protein belongs to a functionally diverse family of winged-helix or forkhead transcription factors that have diverse roles in cellular proliferation, differentiation, and neoplastic transformation. The FOXP1 gene, which maps to 3p14, shows common loss of heterozygosity in breast tumors and is a candidate tumor suppressor gene. However, its role in breast cancer is unknown. EXPERIMENTAL DESIGN: We have therefore investigated the pattern of FOXP1 expression in whole sections from normal (n = 16) and neoplastic (n = 90) breast tissues and correlated the level of expression in 283 invasive breast carcinomas on tissue microarrays with clinicopathological factors and survival. Because a relationship with estrogen receptor (ER) was identified, estrogen (17beta-estradiol) regulation and ER/FOXP1 colocalization was also investigated. RESULTS: Expression of FOXP1 was significantly positively associated with ER (P = 0.03) and negatively with epidermal growth factor receptor (P = 0.01) but no association with age (P = 0.91), lymph node status (P = 0.94), size (P = 0.76), or grade (P = 0.22). In a multivariate analysis of survival, FOXP1 expression was associated with a significantly improved relapse-free (P = 0.03) and borderline overall (P = 0.09) survival. Unlike normal breast, there was common coexpression of FOXP1 and ER in cell lines and tumors, but no 17beta-estradiol (10(-9) m) regulation of FOXP1 in MCF-7 cells was demonstrated. CONCLUSIONS: Our findings support a role for FOXP1 as a potential ER coregulator in human breast carcinoma and suggest that it may also independently regulate additional important pathways that control the progression of breast cancer.